Group Selection: A Review Essay on Does Altruism Exist? by David Sloan Wilson - Robson, Arthur J. (Journal of Economic Literature, 2017)
In response to the question in the title, Does Altruism Exist?, David Sloan Wilson argues forcefully that altruism exists and that the biological mechanism of group selection is responsible. He argues that group selection should be taken especially seriously for humans, since cultural evolution is especially important for us. Economists' view of basic human motivations should then include altruism. Wilson promotes a strong form of pervasive altruism, which seems bound to be inconsistent with many economic phenomena. Although a moderate version of the position he advocates is not easily dismissed, it is unclear what such an extended theory would look like. (JEL D64, Z13)